Examination of the profitability of technical analysis based on moving average strategies in BRICS - Matheus José Silva de Souza; Danilo Guimar\~aes Franco Ramos; Marina Garcia Pena; Vinicius Amorim Sobreiro; Herbert Kimura (Financial Innovation, 2018)
In this paper, we investigated the profitability of technical analysis as applied to the stock markets of the BRICS member nations. In addition, we searched for evidence that technical analysis and fundamental analysis can complement each other in these markets. To implement this research, we created a comprehensive portfolio containing the assets traded in the markets of each BRICS member. We developed an automated trading system that simulated transactions in this portfolio using technical analysis techniques. Our assessment updated the findings of previous research by including more recent data and adding South Africa, the latest member included in BRICS. Our results showed that the returns obtained by the automated system, on average, exceeded the value invested. There were groups of assets from each country that performed well above the portfolio average, surpassing the returns obtained using a buy and hold strategy. The returns from the sample portfolio were very strong in Russia and India. We also found that technical analysis can help fundamental analysis identify the most dynamic companies in the stock market.
Keywords: 650; Technical analysis; Moving average strategies; Automated trading systems; Portfolio analysis; BRICS